Muscular Dystrophy A Concise Guide - Huml, Raymond A.; Huml, Raymond A. (Springer International Publishing : Imprint: Springer, 2015)
This practical and concise guide offers an overview of muscular dystrophy's (MD) complicated features, treatment options and general resources.  New treatments and a greater understanding of proteins and structures associated with MD are discussed along with long-term patient care.  Also included are clinical and developmental challenges within the current regulatory landscape and recent scientific and clinical advances.  Muscular Dystrophy: A Concise Guide offers clinicians, researchers, pharmaceutical executives and patient advocacy groups an easy-to-read reference that provides the necessary perspectives of the care giver and patient.